2012
DOI: 10.1590/s1415-43662012001200015
|View full text |Cite
|
Sign up to set email alerts
|

Semeadora-adubadora: mecanismos de corte de palha e cargas verticais aplicadas

Abstract: Realizou-se este trabalho com o objetivo de avaliar o desempenho dos mecanismos de corte de palha de uma semeadora-adubadora em diferentes coberturas vegetais e cargas verticais aplicadas. O delineamento experimental utilizado foi em blocos ao acaso e esquema fatorial 3 x 4, com 4 repetições. Os trabalhos foram realizados com três diferentes mecanismos de corte de palha (disco liso, disco corrugado e disco ondulado) utilizando-se quatro diferentes cargas verticais (750, 1500, 2250 e 3000 N) em cinco coberturas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
6
0
6
Order By: Relevance
“…The use of smooth coulters reduced soil disturbance by 12.26% when compared with the offset fluted; there was no difference from the treatment without coulters. Mion et al (2009) and Silva et al (2012), while working with different coulters, also found statistical differences between soil disturbance caused by different types of coulters, and the offset fluted coulters also caused more disturbance than the smooth discs.…”
Section: Maximum Furrow Depthmentioning
confidence: 91%
See 1 more Smart Citation
“…The use of smooth coulters reduced soil disturbance by 12.26% when compared with the offset fluted; there was no difference from the treatment without coulters. Mion et al (2009) and Silva et al (2012), while working with different coulters, also found statistical differences between soil disturbance caused by different types of coulters, and the offset fluted coulters also caused more disturbance than the smooth discs.…”
Section: Maximum Furrow Depthmentioning
confidence: 91%
“…Coulters also produce different effects, and according to Silva et al (2012), the offset fluted and smooth coulters generally increase disturbance of the seedbed soil, the effect of the former being more significant. Mion et al (2009) corroborated this statement, since they found significant differences in soil disturbance by these mechanisms, with 0.0015 m² values for 3 Disturbance of Ultisol soil based on interactions between furrow openers and coulters between the rotary planes of the discs, and 70 mm height for the point of contact.…”
Section: Methodsmentioning
confidence: 99%
“…Este resultado é explicado como decorrente do uso do disco de corte ondulado de 12 ondas, que possibilita maior mobilização do solo e, desta forma, exige maior força vertical para atingir maior profundidade (Silva et al, 2012), ou seja, maior massa por linha do que o disco duplo. - (1) Médias seguidas por letras iguais, na linha, não diferem entre si, pelo teste de Tukey, a 5% de probabilidade.…”
Section: Resultsunclassified
“…Levien et al (2011), also concluded that the opening of grooves through the use of hoe type furrow opener increases the demands of tractive force in relation to the employment of the double-disc. Evaluating the straw cutting mechanisms, Silva et al (2012) showed that the offset fluted coulters need a higher horizontal force to break the resistance of the soil in comparison to the smooth disc, possibly because of the design of the disc and its dynamic action on the soil and contact area are different. Besides that, Germino and Benez (2006) concluded that the presence of disc does not change the traction demands by hoe opener, being 0.77 kN for situations with disc and 0.78 kN for the conditions without the mechanism.…”
Section: Introductionmentioning
confidence: 99%